Recent developments in clinimetric instruments - Karen Beeton (2018)
Assessment of impairment and function is essential in order to monitor joint status and evaluate therapeutic interventions in patients with haemophilia. The improvements in the treatment of haemophilia have required the development of more sensitive tools to detect the more minor dysfunctions that may now be apparent. This paper outlines some of the recent developments in this field. The Haemophilia Joint Health Score (HJHS) provides a systematic and robust measure of joint impairment. The MRI Scoring System has been designed to provide a comprehensive scoring system combining both progressive and additive scales. The Functional Independence Score for Haemophilia (FISH) has been developed to assess performance of functional activities and can be used in conjunction with the Haemophilia Activities List (HAL) which provides a self report measure of function. It is recommended that both measures are evaluated as these tools measure different constructs. Further refinement and testing of the psychometric properties of all of these tools is in progress. More widespread use of these tools will enable the sharing of data across the world so promoting best practice and ultimately enhancing patient care. © 2006 The Authors Journal compilation © 2006 Blackwell Publishing Ltd.